(4π₯π¦ + 3π¦2 )ππ₯ + π₯(π₯ + 2π¦)ππ¦ = 0
"(4xy+3y^2)_y=4x+6y\\neq (x(x+2y))_x=2x+2y"
So, the equation is not exact.
"u=y\/x"
"y'=xu'+u"
"3x^2u^2+2x^2(xu)'+4x^2u+x^2(xu)'=0"
"2x^3uu'+x^3u'+5x^2u^2+5x^2u=0"
"\\frac{(2u+1)u'}{5u(u+1)}=-\\frac{1}{x}"
"\\int\\frac{2u+1}{5u(u+1)}du=-\\int\\frac{1}{x}dx"
"\\frac{ln(u^2+u)}{5}=c-lnx"
"u_1=-\\frac{\\sqrt{c_1\/x+1}+1}{2}"
"u_2=\\frac{\\sqrt{c_1\/x+1}-1}{2}"
"y_1=-\\frac{\\sqrt{c_1\/x+1}+1}{2}x"
"y_2=\\frac{\\sqrt{c_1\/x+1}-1}{2}x"
Comments
Leave a comment